Stretchable energy storage devices : from materials and structural design to device assembly - Gong, Xuefei (2021)
Stretchable energy storage devices (SESDs) are indispensable as power a supply for next-generation independent wearable systems owing to their conformity when applied on complex surfaces and functionality under mechanical deformation. Structural strategies with underlying fundamental mechanics to achieve stretchability and material synthesis for stretchable electrodes and separators as building blocks in the fabrication of SESDs are briefly introduced in this review. Representative SESDs including stretchable supercapacitors and stretchable Li-based and Zn-based batteries are also summarized from the perspective of design strategy and performance optimization in terms of voltage output, energy density and capacity retention under mechanical strain. Finally, challenges and future development directions in this promising field are presented.